Adaptation to climate change for food security in the lower Mekong Basin - Mainuddin, M.; Kirby, M.; Hoanh, Chu Thai (Springer, 2011)
Variability in water cycles driven by climate change is considered likely to impact rice production in the near future. Rice is the main staple food for the population in the lower Mekong Basin and the demand for food is expected to grow due to increase in population. This paper examines the impact of climate change on rice production in the lower Mekong Basin, evaluates some widely used adaptation options, and analyses their implications for overall food security by 2050. Climate change data used in the study are the future climate projection for two IPCC SRES scenarios, A2 and B2, based on ECHAM4 General Circulation Model downscaled to the Mekong region using the PRECIS (Providing Regional Climates for Impact Studies) system. In general, the results suggest that yield of rainfed rice may increase significantly in the upper part of the basin in Laos and Thailand and may decrease in the lower part of the basin in Cambodia and Vietnam. Irrigated rice may not be affected by climate change if increased irrigation requirements are met. Negative impact on the yield of rainfed rice can be offset and net increase in yield can be achieved by applying widely used adaptation options such as changing planting date, supplementary irrigation and increased fertilizer input. Analysis of the projected production, considering population growth by 2050, suggests that food security of the basin is unlikely to be threatened by the increased population and climate change, excluding extreme events such as sea level rise and cyclones.